2018
DOI: 10.5897/ajbr2017.0981
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriostatic and Bactericidal effects of ethyl acetate root bark extract of Terminalia avicennioides on Methicillin-resistant Staphylococcus aureus

Abstract: Root bark extract of Terminalia avicennioides was obtained by cool maceration with 750 ml n-hexane, chloroform, ethyl acetate and methanol, independently for 48 h using soxhlet extractor. ATCC 33591 standard strains of methicillin-resistant Staphylococcus aureus (MRSA) was used. Strain resistance to methicillin/oxacillin antibiotic was verified by a retest of its sensitivity to oxacillin antibiotic. The antimicrobial test and zone of inhibition were determined using the agar well diffusion method. The isolated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
2
2
0
Order By: Relevance
“…Similarly, the differences exhibited by the extracts of different solvents could imply that the extracts with higher activities extracted more of the active principles (Babayi et al 2004). The antibacterial activity displayed by T. avicennioides in this study was most likely mediated by similar constituents identified in the report by Adim et al (2018) as the plant in their study was sampled from the same location as ours. However, while our study utilized both crude extracts and fractions, Adim et al (2018) described ethylacetate extract.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Similarly, the differences exhibited by the extracts of different solvents could imply that the extracts with higher activities extracted more of the active principles (Babayi et al 2004). The antibacterial activity displayed by T. avicennioides in this study was most likely mediated by similar constituents identified in the report by Adim et al (2018) as the plant in their study was sampled from the same location as ours. However, while our study utilized both crude extracts and fractions, Adim et al (2018) described ethylacetate extract.…”
Section: Discussionsupporting
confidence: 81%
“…The antibacterial activity displayed by T. avicennioides in this study was most likely mediated by similar constituents identified in the report by Adim et al (2018) as the plant in their study was sampled from the same location as ours. However, while our study utilized both crude extracts and fractions, Adim et al (2018) described ethylacetate extract.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The anti-carcinogenic properties of Momordica charantia have also been reported [16,17]. It is has been established that researcher ' s interest for scientific investigations on plant based system is motivated by the bioactive secondary metabolites produced either by the fruit, seeds, leaves, roots and or bark parts of the plant [18]. The tradomedical use of plant-based system is emerging but needs scientific verification to validation the practice.…”
Section: Biomedical Research 2019; 30 (4): 529-537mentioning
confidence: 99%